Taxonomic revision of the African genus Trechosiella Jeannel (Coleoptera: Carabidae: Trechinae) - Geginat, Gernot (Zootaxa, 2013)
The genus Trechosiella Jeannel, 1960 (Carabidae: Trechinae) is revised. In addition to the known species T. laetula (Péringuey, 1898), T. scotti (Jeannel, 1937), T. basilewskyi Jeannel, 1960 and T. katicola Jeannel, 1964, T. endroedyyoungai spec. nov., T. oligophthalma spec. nov. and T. scotti swartbergensis subspec. nov. are newly described. Trechosiella laetula peringueyi (Jeannel, 1926) is recognized as a new synonym of T. laetula sensu stricto. Trechosiella macroptera Casale, 1986 is demoted to become a subspecies of T. scotti, as T. scotti macroptera status demotus. An identification key to the known species and subspecies of Trechosiella and a distribution map of the southern African taxa are provided.